The Loss Of Identity In Emily Bronte‘S Wuthering Heights and K. S. Maniam‘S The Return in relation to communication issues: A critical analysis - Abda Alsalim, Hafudh Farhood (2021)
The Post-world War II was the period of an act to ask for decolonisation and freedom of nations, which were hitherto under colonial rule. These communities wanted to move forward in the direction of reforming their social and individual identities. Therefore, the question of identity became one of the most critical issues in postcolonial literature as its crisis existed in all postcolonial communities. The purpose of this study is to explore the loss of identity that individual encounters during the process of searching for an identity. This is because lack of communication and physical mobility usually amplify the spiritual or psychological sense of alienation, leading to loss of identity. In this study, the researcher adopted the postcolonial criticism (Homi Bhabha‘s Ambivalence and Edward Said‘s Orientalism) and the psychoanalytic criticism (Freud‘s Defense Mechanisms and Kristeva‘s Abjection). This study analysed two postcolonial novels (Emily Bronte‘s Wuthering Heights and K.S Maniam‘s The Return) tracing the themes of loss of identity and the effect of communication in the role of the behaviour of the characters. The two novels were analysed in a systematic approach based on the principles of the qualitative research technique that was embraced in conducting the thematic analysis of the novels. The nature of the study was interpretative in terms of analysing the texts. The study clarified the influence of colonialism on identity, social, psychological, and political facets of colonised communities. As the coloniser imposed his language on the colonised, misunderstanding and lack of communication became part of the colonised‘s life. Therefore, the main reason behind the loss of identity in both novels was demonstrated through the lives of the two main characters (Heathcliff in Wuthering Heights and Ravi in The Return). The duo was slave and migrant who were exposed to new cultures. It was difficult for them to cope with the new cultures as communication challenges set in amidst the quest for their own identities. The psychological trauma experienced by the characters showed the crisis of identity the colonised communities suffered from. This study is regarded as the first approach grouping these two novels to be studied together as postcolonial novels from two viewpoints: the coloniser and the colonised to show the crisis of identity. Besides, a new psychological theory (Kristeva‘s Abjection) was applied to examine the psychological impacts of colonialism on the colonised. Lastly, the study demonstrated the consequences of random migration on people. Thus, it is a call to mitigate the migration of young people from Iraq to foreign countries.